Increased Reactive Oxygen Species and Cell Cycle Defects Contribute to Anemia in the RASA3 Mutant Mouse Model scat - Hartman, Emily S.; Brindley, Elena C.; Papoin, Julien; Ciciotte, Steven L.; Zhao, Yue; Peters, Luanne L.; Blanc, Lionel (Frontiers in Physiology, 2018)
RASA3 is a Ras GTPase activating protein that plays a critical role in blood formation. The autosomal recessive mouse model scat (severe combined anemia and thrombocytopenia) carries a missense mutation in Rasa3. Homozygotes present with a phenotype characteristic of bone marrow failure that is accompanied by alternating episodes of crisis and remission. The mechanism leading to impaired erythropoiesis and peripheral cell destruction as evidenced by membrane fragmentation in scat is unclear, although we previously reported that the mislocalization of RASA3 to the cytosol of reticulocytes and mature red cells plays a role in the disease. In this study, we further characterized the bone marrow failure in scat and found that RASA3 plays a central role in cell cycle progression and maintenance of reactive oxygen species (ROS) levels during terminal erythroid differentiation, without inducing apoptosis of the precursors. In scat mice undergoing crises, there is a consistent pattern of an increased proportion of cells in the G0/G1 phase at the basophilic and polychromatophilic stages of erythroid differentiation, suggesting that RASA3 is involved in the G1 checkpoint. However, this increase in G1 is transient, and either resolves or becomes indiscernible by the orthochromatic stage. In addition, while ROS levels are normal early in erythropoiesis, there is accumulation of superoxide levels at the reticulocyte stage (DHE increased 40% in scat; p=0.02) even though mitochondria, a potential source for ROS, are eliminated normally. Surprisingly, apoptosis is significantly decreased in the scat bone marrow at the proerythroblastic (15.3%; p=0.004), polychromatophilic (8.5%; p=0.01), and orthochromatic (4.2%; p=0.02) stages. Together, these data indicate that ROS accumulation at the reticulocyte stage, without apoptosis, contributes to the membrane fragmentation observed in scat. Finally, the cell cycle defect and increased levels of ROS suggest that scat is a model of bone marrow failure with characteristics of aplastic anemia.